Critical factors of employee engagement in enhancing job satisfaction among the UAE’S employees - Abdulrahman Alafeefi, Fatima Rashad (2024)
Job satisfaction among employees is a critical objective for human resources departments, vital for the success of any organization. Job satisfaction specifically refers to an employee's contentment with their individual job roles, tasks, and responsibilities. It delves into how employees feel about the work they do, their immediate work environment, relationships with colleagues, and the tasks they are responsible for completing. Employee satisfaction, on the other hand, is a broader concept. It encompasses job satisfaction but extends to cover the overall satisfaction of an employee within the entire organization. Employee satisfaction takes into account not only the job itself but also various other factors such as the work culture, leadership, communication within the organization, opportunities for skill development, work-life balance, job security, benefits, and the organization's policies and practices. Employee satisfaction is gaining prominence, especially in the face of fierce talent competition. Disengaged employees can lead to dissatisfaction and ultimately a high turnover rate, hampering organizational growth. Despite this, there has been limited research on job satisfaction linked to employee engagement in the UAE. This study aims to develop an employee engagement model to enhance employee satisfaction within organizations. The study has three primary objectives. First, it seeks to identify the attributes of employee engagement that enhance job satisfaction among employees. Second, it aims to design an employee empowerment model that fosters job satisfaction within the organization. Third, it intends to validate the proposed model's effectiveness in enhancing overall employee satisfaction within the organization. The research follows a three-phase process-based design: analysis, design and development, and evaluation and testing. Conducted in the UAE, the study surveyed 381 respondents. Utilizing regression models, the data were analyzed to test six hypotheses. The results revealed three significant factors: working environment, leadership, and perceived organizational support. Conversely, training and development, rewards, and salary were found to be insignificant in influencing employee job satisfaction. The analysis demonstrated a robust relationship between the factors in the employee engagement model and employee job satisfaction, with an R-value of 0.781, validating the proposed model. In essence, the developed employee engagement model serves as a valuable reference for organizational leaders and management. It provides guidelines for improving the working environment, leadership, and organizational support, enabling effective employee engagement strategies to be implemented, ultimately leading to enhanced employee satisfaction within the organization.